Kemampuan Literasi Awal Anak Usia Dini di RA Bintang Zuhra Takengon - Suminah; Mardiana; Riza, Muhammad (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
RA Bintang Zuhra Takengon is one of the schools in the central region of Aceh, Indonesia, with the address Kampung Pinangan, Kebayakan District. Literacy is a combination of the ability to read, think and write. These skills are applied when interacting with other parties in various contexts. The problems that occur, especially at RA Bintang Zuhra Takengon, are that there are still some children who have difficulty in reading skills, namely memorizing letters, recognizing letters and distinguishing letters. The aim of the author is to see how children improve in their reading abilities, namely memorizing letters, recognizing letters and distinguishing letters. The purpose of this research is to improve children's literacy skills at RA Bintang Zuhra Takengon. This research uses a qualitative descriptive method to see where children make mistakes in recognizing early childhood reading and writing literacy. The subjects were taken randomly based on the categories Not Yet Developing (BB, Starting to Develop (MB), Developing According to Expectations (BSH) and Developing Very Well (BSB). Determination of the three assessment categories was carried out by giving tests to 13 children. Results and conclusions of this research was the first meeting with a result of 30.77% in the BSB-BSH category, MB category 23.08%, BB 46.15%. The second meeting was 30.77% in the BSB-BSH category, MB category 30.77%, BB 38.46. %. The third meeting of the children's BSB-BSH score category was 53.84%, the MB category was 15.39%, and the BB score category was 30.77%.